Performance of tree species in two arboretums of the Institute of Animal Science - Ach?n, Geovanis; Febles, Gustavo; Ruiz, Tom?s; Alonso, Jatnel; Noda, Aida (Cuban Journal of Agricultural Science, 2011)
Information is provided about the performance of tropical trees and shrubs that can be used in agricultural areas for different productive aims. The technique of multivariate analysis (clusters) was applied for data processing. The arboretum 1 was sown with 50 species in the Experimental Center of Pastures and Forages, and the arboretum 2 with 36 species in the cattle unit ?Gen?tico 4?, both facilities are located at the Institute of Animal Science. Out of all the species of the arboretum 1, Adenanthera pavonina, Enterolobium contortisiliqum, Sophora tomentosa, Siderocarpus flexicaulis, Bauhinia purpurea, Pongamia pinnata and Lonchocarpus punctatus were noteworthy due to their higher survival (100 %), growth, and lower acceptance. In the arboretum 2, Caesalpinea paucijuga, Peltophorum affricanum, Enterolobium contortisiliquum, Casia moschata, Albizia lebbekoides, Colvillea racemosa and Moringa ole?fera reached greater height, and agreed with those of higher survival. The most consumed genera in the two arboretums were Erythrina, Bauhinia and Albizia. The species of greatest intake in the two arboretums was Albizia caribeae, and those of lowest, Enterolobium contortisiliquum and Siderocarpus flexicaulis. Further studies are recommended about those of best performance, mainly in the arboretum 1, which could have insecticide action. Key words: arboretum, survival, growth, acceptability